PREFERENTIAL EROSION OF BLACK CARBON ON STEEP SLOPES WITH SLASH AND BURN AGRICULTURE - Rumpel C.; Planchon O.; Bernadou J.; Mariotti A.; Chaplot V.; Valentin C. (My University, 2006)
In this study we investigated the quantitative and qualitative aspects of soil organic matter (SOM) losses caused by water erosion within a small catchment in Northern Laos, under steep slopes and slash and burn agriculture. The soils in the region have a high contribution of black carbon to soil organic matter and high erosion rates. The aim of the study was to quantify the erosion of black carbon and to identify the processes involved. The conceptual approach included the measurement of contents of SOM, black carbon and mineral bound SOM in bulk soils, sediments eroded from 1 m2 plots and in sediments at the outlet of the 0.6 ha catchment. Additionally, the enrichment factors of bulk SOM, BC and mineral bound SOM were calculated for eroded sediments. Carbon content of eroded sediments was higher than carbon content in bulk soil. The C enrichment factors in the sediments eroded from 1 m2 plots ranged between 1.7 and 2.7, which confirms that SOM rich material such as clay or silt along with particulate organic matter such as black carbon and plant debris is preferentially eroded. At the watershed level a mean carbon enrichment factor of 1.5 showed that part of the eroded carbon is lost from the watershed. Analysis of the carbon types showed that mineral bound SOM is representing on average 30% and black carbon 15% of the carbon of the bulk soil. Mineral bound organic matter is not eroded preferentially from the soil. Enrichment factors from 1.1 to 1.8 were recorded for black carbon in sediments eroded from 1 m2 plots. At the watershed level, black carbon represents 30% of carbon in eroded sediments. The average enrichment factor of black carbon in sediments eroded from the watershed is 2.3 compared to bulk soil C content. These results show a continuous enrichment of sediments in black carbon during the whole process of soil erosion. The preferential erosion of black carbon compared to other SOM types can be explained by its light nature, absence of mineral interactions right after its formation and its resistance to biodegradation during transport. Carbon erosion in these tropical soils may thus lead to a decrease of their ability to act as a sink for CO2 due to the preferential exportation of a very stable SOM form. These results further suggest that erosion of black carbon could be a crucial process determining its fate in terrestrial ecosystems. Moreover, black carbon erosion could be conceptually simpler than soil erosion and could therefore be tackled by specific models. © 2005 Elsevier B.V. All rights reserved.
Keywords: BLACK CARBON; EROSION; ORGANIC MATTER; TROPICAL SLOPING LAND